1997
DOI: 10.1086/514084
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Spread of Human Immunodeficiency Virus‐Related Multidrug‐Resistant Tuberculosis in Buenos Aires

Abstract: A steep upsurge of human immunodeficiency virus (HIV)-associated multidrug-resistant tuberculosis (MDR-TB) was recently observed at a referral treatment center in Buenos Aires City. Between January 1994 and June 1995, TB isolates resistant to at least five drugs were recovered from 101 of 272 HIV-infected inpatients. Highly resistant isolates from 77 patients underwent restriction fragment length polymorphism study with IS6110. After cross-contamination was eliminated, a single TB strain was found to have caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 13 publications
(2 reference statements)
3
89
1
Order By: Relevance
“…Multidrug resistance (MDR, resistant to at least INH and RIF) will thus occur mainly in circumstances where treatment is not optimal. Reports of nosocomial outbreaks of MDR-TB in institutions such as hospitals (10)(11)(12)(13) and prisons (14) and in the United States, Europe, and developing countries (15,16) have focused attention on MDR-TB as a major health issue. Infection followed by active MDR-TB in health care workers after exposure to patients with MDR-TB (17)(18)(19), and outbreaks within communities have also been reported (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug resistance (MDR, resistant to at least INH and RIF) will thus occur mainly in circumstances where treatment is not optimal. Reports of nosocomial outbreaks of MDR-TB in institutions such as hospitals (10)(11)(12)(13) and prisons (14) and in the United States, Europe, and developing countries (15,16) have focused attention on MDR-TB as a major health issue. Infection followed by active MDR-TB in health care workers after exposure to patients with MDR-TB (17)(18)(19), and outbreaks within communities have also been reported (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…For example, an HIV seropositive patient developed primary tuberculosis with a multidrug resistant (MDR) strain in San Francisco. This patient had been hospitalized in Buenos Aires, Argentina, the previous year, during the time of a reported large outbreak of MDR-TB (12). The San Francisco strain was found to have exactly the same IS6110-RFLP pattern and antibiotic resistance profile as the Buenos Aires strains (M. Burgos, unpublished data).…”
Section: Is6110 Rflpmentioning
confidence: 95%
“…Molecular epidemiology has also highlighted the epidemic spread of drug-resistant strains among hospitalized patients (12,(56)(57)(58)(59). Studies conducted on patients hospitalized in New York City revealed that more than one third of patients with multidrug-resistance had clustered RFLP patterns, suggesting recent transmission of M. tuberculosis (60).…”
Section: Transmission Of Drug Resistancementioning
confidence: 99%
“…They identified various infectious chains of contact that, starting in a bar that played the role of a turntable, moved out rapidly into several areas such as housing for homeless men and alcoholics and a tank-cleaning firm.This study can be considered as a model because it combines detailed clinical and epidemiological data and phenotypical and molecular studies. Nowadays, numerous outbreaks continue to be identified in various public areas such as hospitals, schools, bars, prisons, nursing homes, and homeless shelters in developed and developing countries [38,52,90,92,105,116,120,153,159,178]. These studies were also able to identify risk factors for TB transmission.…”
Section: Clinical and Epidemiological Relevance Of Molecular Epidemiomentioning
confidence: 99%
“…DNA fingerprinting can determine that in many of these outbreaks, the susceptibility of HIV-positive patients to tuberculosis infections and the accelerated breakdown to disease often result in more rapid transmission of the infection [42,50,55,149,153,165]. Furthermore, the study of MTB isolates obtained from AIDS patients by fingerprinting showed that reinfection and relapse both occur in HIV-infected patients, as the susceptibility to superinfections will most likely be related to the immune status of the patient.…”
Section: Use Of Genotyping To Study the Impact Of Hiv/aids And Drug Rmentioning
confidence: 99%